Measures against carbon leakage: Combining output-based allocation with consumption taxes - Christoph Böhringer; Knut Einar Rosendahl; Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2024)
Countries with ambitious climate targets are concerned about carbon leakage to countries with more lenient or no carbon pricing. A common policy measure against leakage is output-based allocation of emissions allowances, whose effectiveness could be further enhanced by consumption taxes levied on the carbon intensity of goods. We combine theoretical and numerical analysis to derive optimal combinations of output-based allocation and consumption taxes for different assumptions on the stringency of emissions reduction targets, the coverage of emissions in regulated sectors, and their trade exposure. A key analytical finding is that output-based allocation and consumption taxes are complements rather than substitutes, i.e., the extent of output-based allocation should be higher if combined with a consumption tax. A key numerical finding is that the optimal output-based allocation and consumption tax rates should be set at almost the same rate and increase substantially with the stringency of the emissions reduction targets.
Keywords: D61; F18; H23; Q54; 330; Carbon leakage; output-based allocation; consumption taxes